ISLAMIC DA'WA, SOCIAL IDENTITY AND VIOLENCE AGAINST AHMADIYYA COMMUNITY IN LOMBOK - Afifudin Adnan; Kadri Kadri; Siti Nurul Yaqinah (TAJDID: Jurnal Pemikiran Keislaman dan Kemanusiaan, 2023)
This article discusses Islamic da'wa, social identity and violence against Ahmadiyya community in Lombok. This article is field research using qualitative methods and a case study approach. To analyze this phenomenon, this article uses social identity theory. It highlights how individuals develop and understand their identity in relation to specific social groups. The stigma and identity of Ahmadis as a group considered heretical by mainstream Muslims means that they are often victims of violence. Since post-reform until now, the Ahmadiyya community has experienced displacement from their hometowns, such as the violence in Pancor East Lombok in 2002, and Ketapang Gerung Village, Lingsar District, West Lombok in 2006 and 2010, and finally in Sakra East Lombok 2021. The results of this study revealed that: First, violence against Ahmadiyya in Lombok was caused by conservative Islamic proselytizing patterns. Although in fact Islamic groups in Lombok are moderate. Second, strengthening the social identity distinction between the Aswaja and Ahmadiyya groups in social relations. Thus, Ahmadis become a minor identity victimized, so they do not get freedom in the public sphere, even isolated by mainstream Islamic groups.